Effect of ethephon (2 chloro ethylphosphonic acid) applied to the trees on fruit ripening in 'Golden Nugget' loquat (Eriobotrya japonica Lindl.) - Undurraga P.; Olaeta J.A. (First international symposium on loquat, 2003)
The effect of ethephon applied on leaves on fruit ripening was studied in loquat cv. 'Golden Nugget'. Foliar sprays were done on 4 year old trees early in the growing season (40, 80, and 120 ppm). Two groups were made after spraying: fruits with an equatorial diameter greater or equal to 40 mm, (green to yellowish-green exocarp) (M1); and fruits with a 25-40 mm equatorial diameter (green exocarp) (M2). Weekly samples were analysed for soluble solids and titratable acidity. Every two days fruit ripening was evaluated. Sensory evaluation was done at the final harvest, when fruit was fully ripe. Trees were also monitored for leaf, flower or developing fruit abscission. M1 fruits, with 120 ppm ethephon, reached ripeness 7 days earlier than the control. Increasing ethephon rates also altered the acidity of the M2 fruits. No effects on vegetative development were detected, with no symptoms of abscission in leaves nor developing flowers or fruit.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)